Shear and degradation behavior of rail track ballast contaminated with fines: An experimental study. - Navaratnarajah, S.K.; Venuja, S. (International society for Soil Mechanics & Geotechnical Engineering, 2020)
Rail transport is one of the highly demanded transport modes due to its safety, reliability and economic profits. The ballast layer, major component by weight and volume, effectively transmits the train exerted loads from sleepers to the underlying layer at a minimal level. Ballast is degraded over time because of repetitive train loads. Ballast fouling is one of the major factors that affect the load-bearing capacity of the ballast layer as well as deters the permeability. This experimental based research primarily analyzes the changes in shear and degradation behavior of rail track ballast after fouling by other foreign material. The outcomes of the laboratory tests clearly indicate that fouling by sand increases the overall density of the sample, therefore, increases the shear strength and clay fouling acts as a lubricant thus reduces the shear strength. Ballast breakage under static loading increases with the increment in vertical load and decreases with fouling agents.